A Scoping Review of Antimicrobial Usage and Antimicrobial Resistance in Beef Cow-Calf Herds in the United States and Canada - Barbara Wilhelm; Jayce Fossen; Sheryl Gow; Cheryl Waldner (MDPI AG, 2023)
Background: The magnitude and knowledge gaps regarding antimicrobial use (AMU) and antimicrobial resistance (AMR) have not been summarized for the North American cow-calf production sector, although estimates of AMU and AMR are essential to AMR risk analysis. The objectives of this scoping review were to map AMU and AMR in the beef cow-calf sector in Canada and the United States, summarize published AMU/AMR predictors, and identify research gaps. Methods: An electronic search was conducted of four bibliographic databases and Google Scholar, augmented by a hand-search of captured studies. Results: Twenty-three of three-hundred and forty-three publications screened advanced to data extraction. Of these, 10 were conducted in the USA and 13 in Canada. Thirteen studied AMR and twelve studied AMU, with two reporting both. Of twelve captured AMU studies, nine presented counts of herd AMU by antimicrobial class or specific antimicrobial. Antimicrobial resistance in Escherichia coli (E. coli) was reported in nine studies. Risk factors for AMU include herd size, vaccine use, and start date of calving season. Conclusions: Overall, a small number of AMR studies were available for synthesis in primarily one population (cows) reporting E. coli AMR. Additional studies targeting reasons for AMU in calves, the impact of management procedures on AMU, potential environmental AMR sources, and AMR in respiratory pathogens and enteric organisms other than E. coli for pre-weaning calves are required to inform AMR risk mitigation strategies.